The expansion of endoscopic submucosal dissection in France: A prospective nationwide survey. Issue 1 (February 2017) - Barret, Maximilien; Lepilliez, Vincent; Coumaros, Dimitri; Chaussade, Stanislas; Leblanc, Sarah; Ponchon, Thierry; Fumex, Fabien; Chabrun, Edouard; Bauret, Paul; Cellier, Christophe; Coron, Emmanuel; Bichard, Philippe; et al.
Introduction: Early reports of endoscopic submucosal dissection (ESD) in Europe suggested high complication rates and disappointing outcomes compared to publications from Japan. Since 2008, we have been conducting a nationwide survey to monitor the outcomes and complications of ESD over time. Material and methods: All consecutive ESD cases from 14 centers in France were prospectively included in the database. Demographic, procedural, outcome and follow-up data were recorded. The results obtained over three years were compared to previously published data covering the 2008–2010 period. Results: Between November 2010 and June 2013, 319 ESD cases performed in 314 patients (62% male, mean (±SD) age 65.4 ± 12) were analyzed and compared to 188 ESD cases in 188 patients (61% male, mean (±SD) age 64.6 ± 13) performed between January 2008 and October 2010. The mean (±SD) lesion size was 39 ± 12 mm in 2010–2013 vs 32.1 ± 21 for 2008–2010 ( p  = 0.004). En bloc resection improved from 77.1% to 91.7% ( p  < 0.0001) while R0 en bloc resection remained stable from 72.9% to 71.9% ( p  = 0.8) over time. Complication rate dropped from 29.2% between 2008 and 2010 to 14.1% between 2010 and 2013 ( p  < 0.0001), with bleeding decreasing from 11.2% to 4.7% ( p  = 0.01) and perforations from 18.1% to 8.1% ( p  = 0.002) over time. No procedure-related mortality was recorded. Conclusions: In this multicenter study, ESD achieved high rates of en bloc resection with a significant trend toward better outcomes over time. Improvements in lesion delineation and characterization are still needed to increase R0 resection rates.